Design and commissioning of the first superconducting undulator for the BioSAXS beamline at the Australian Synchrotron - Yaw-Ren Eugene Tan; Sina Porsa; David Zhu; Christina Kamma-Lorger; Andrew J. Clulow; Sara Casalbuoni; Andreas Grau; Nicole Glamann; Achim Hobl; Martin Krichler (Journal of Synchrotron Radiation, 2025)
A 1.6 m-long 16 mm-period superconducting undulator (SCU16) has been installed and commissioned at the Australian Synchrotron. The SCU16, developed by Bilfinger, is based on the SCU20 currently operating at Karlsruhe Institute of Technology (KIT). The SCU16 is conduction cooled with a maximum on-axis field of 1.084 T and a fixed effective vacuum gap of 5.5 mm. The design, commissioning experience and performance of one of the longest superconducting undulators at a light source are presented.